Which expression has the same value as 3x 1 when x = 4?

Question

Asked 7/12/2019 12:11:36 AM

Updated 274 days ago|7/15/2023 12:37:26 AM

2 Answers/Comments

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Score .8977

Question

Asked 7/12/2019 12:11:36 AM

Updated 274 days ago|7/15/2023 12:37:26 AM

2 Answers/Comments

Rating

3

To find the expression that has the same value as 3x + 1 when x = 4, we substitute the value of x into each expression and check which one gives the same result.

Let's evaluate each expression:

Expression 1: x + 13

Substituting x = 4: 4 + 13 = 17

Expression 2: x + 4

Substituting x = 4: 4 + 4 = 8

Expression 3: (x + 22)/2

Substituting x = 4: (4 + 22)/2 = 26/2 = 13

Expression 4: (x + 20)/2

Substituting x = 4: (4 + 20)/2 = 24/2 = 12

From the above calculations, we can see that the expression (x + 22)/2 has the same value as 3x + 1 when x = 4, which is 13.

Therefore, the correct expression is (x + 22)/2.

Let's evaluate each expression:

Expression 1: x + 13

Substituting x = 4: 4 + 13 = 17

Expression 2: x + 4

Substituting x = 4: 4 + 4 = 8

Expression 3: (x + 22)/2

Substituting x = 4: (4 + 22)/2 = 26/2 = 13

Expression 4: (x + 20)/2

Substituting x = 4: (4 + 20)/2 = 24/2 = 12

From the above calculations, we can see that the expression (x + 22)/2 has the same value as 3x + 1 when x = 4, which is 13.

Therefore, the correct expression is (x + 22)/2.

Added 274 days ago|7/15/2023 12:36:56 AM

This answer has been confirmed as correct and helpful.

3

Combine like terms by adding or subtracting the coefficients of the same variable term.

The correct next step is to combine the like terms by adding the coefficients of the k^2 terms and the coefficient of the k term:

-8k^2 + k + 3k^2 = (-8 + 3)k^2 + k = -5k^2 + k

Therefore, the next correct step when simplifying the expression -8k^2 + k + 3k^2 is -5k^2 + k.

The correct next step is to combine the like terms by adding the coefficients of the k^2 terms and the coefficient of the k term:

-8k^2 + k + 3k^2 = (-8 + 3)k^2 + k = -5k^2 + k

Therefore, the next correct step when simplifying the expression -8k^2 + k + 3k^2 is -5k^2 + k.

Added 274 days ago|7/15/2023 12:37:26 AM

This answer has been confirmed as correct and helpful.

Kyla ran at a rate of 1 mile/13 minutes. She ran a total of 26 minutes. Which equation can Kyla use to find the total distance that she ran? Use the distance formula D = R T. **Weegy:** Kyla ran at a rate of 1 mile/13 minutes. She ran a total of 26 minutes. The total distance she ran is:D = R x T
= (1 mile / 13 minutes) x (26 minutes) = 1 mile x (26 minutes / 13 minutes) = 1 mile x 2= 2 miles. (More)

Question

Expert Answered

Asked 7/11/2019 11:50:32 PM

0 Answers/Comments

f Mary deposits $275 in principal at an interest rate of 3.2 percent, how much interest will she earn in one year?

Question

Not Answered

Updated 12/4/2020 8:49:39 PM

1 Answer/Comment

If Mary deposits $275 in principal at an interest rate of 3.2 percent, the amount of interest she will earn in one year is $8.80.

3.2*275/100 = 8.80.

3.2*275/100 = 8.80.

Added 12/4/2020 8:49:39 PM

This answer has been confirmed as correct and helpful.

If Juan purchased three 24-ounce cans of motor oil for $10.80, how much did he pay per ounce? **Weegy:** If Juan purchased three 24-ounce cans of motor oil for $10.80, he paid $0.45 per ounce. (More)

Question

Updated 2/20/2021 6:41:14 AM

1 Answer/Comment

If Juan purchased three 24-ounce cans of motor oil for $10.80,he pay per ounce $0.15

$10.80/ (24 *3) = $0.15

$10.80/ (24 *3) = $0.15

Added 2/20/2021 6:41:12 AM

This answer has been confirmed as correct and helpful.

7 × (–3) × (–2)2 = ?
**Weegy:** 7+3=10 (More)

Question

Updated 10/12/2020 6:29:46 AM

1 Answer/Comment

7 × (–3) × (–2)2

= 7 × (–3) (- 4)

= -21 (- 4)

= 84

= 7 × (–3) (- 4)

= -21 (- 4)

= 84

Added 10/12/2020 6:29:46 AM

This answer has been confirmed as correct and helpful.

39,050,484

questions answered

There are no comments.